First-Trimester Abortion Complications: Simulation Cases for OB/GYN Residents in Sepsis and Hemorrhage - Armide Storey; Katharine White; Kelly Treder; Elisabeth Woodhams; Shannon Bell; Rachel Cannon (Association of American Medical Colleges, 2020)
Introduction Serious complications associated with first-trimester abortions are rare. The US mortality rate for these procedures is 0.7 per 100,000, primarily due to infection and hemorrhage. While complications are unlikely to arise during training, residents must be prepared to manage them in practice. To address this, we developed a 2-hour simulation-based abortion complication curriculum for OB/GYN resident learners. Methods OB/GYN residents participated in three sessions: a case-based didactic reviewing institutional aspiration abortion practice and preop preparation; an in-vivo aspiration abortion hemorrhage simulation; and an interdepartmental postabortal sepsis simulation. Participants completed surveys before and after their participation that evaluated clinical knowledge, and self-rated competence in, and preparedness for, managing first-trimester abortion complications. Results Resident learners (N = 26) represented all four classes of OB/GYN residents. Residents initially showed stronger clinical knowledge in managing postabortal hemorrhage than sepsis (90% vs. 62%, p < .001). Clinical knowledge improved following the sepsis simulation (62% to 91%, p < .001), and remained strong but unchanged after the hemorrhage simulation (90% to 87%, p = .3). Resident self-assessments of competence and preparedness were significantly improved after both the hemorrhage (p = .006) and sepsis (p = .002) simulations. Learners reported that the simulation increased their level of comfort in managing these complications in their future practice. Discussion Postabortal hemorrhage and sepsis simulations increased OB/GYN residents' knowledge, comfort, and preparedness for managing rare complications of first-trimester abortions. In-vivo simulation and interdepartmental collaboration were novel aspects of these simulations that may facilitate increased preparedness and management skills.